Bullous disorders due to hereditary or acquired desmosome or hemidesmosome impairment - Kansky, Aleksej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Some aspects of the pathogenetic mechanisms of autoimmune bullous disorders aswell as of bullous hereditary disorders are shortly reviewed. The known components of desmosomes and hemidesmosomes, to which specific autoantibodies are directed in autoimmune disorders, are listed. The molecular deficiencies of demosome and hemidesmosome components incriminated to cause hereditary bullous disorders, are also mentioned. The authors believe that clinicians should be familiar with the newest development in basic sciences concerning the pathogenetic role of desmosome and hemidesmosome.
Keywords: Autoantibodies; dermatologija; Desmosomes; Immunology; kožne bolezni; Skin diseases, vesiculobullous